Literary translation in Modern Iran : a sociological study - Haddadian-Moghaddam, Esmaeil (Benjamins translation library, 2014)
Literary Translation in Modern Iran: A sociological study is the first comprehensive study of literary translation in modern Iran, covering the period from the late 19th century up to the present day. By drawing on Pierre BourdieuN's sociology of culture, this work investigates the people behind the selection, translation, and production of novels from English into Persian. The choice of novels such as Morier's The Adventures of Hajji Baba of Ispahan, Austen's Pride and Prejudice, and Vargas Llosa's The War of the End of the World.